Konsep Kepemimpinan Perempuan dalam Islam dan Katolik : Analisis Kepemimpinan Megawati dan Aquino - Nyi Ayu Khofifah; M. Ikhsan Tanggok (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the concept of women's leadership from an Islamic and Catholic perspective and how religious values ​​influence the acceptance and legitimacy of women's leadership in the public sphere. Using a qualitative approach using a desk study method, this study analyzes religious texts, scientific literature, and case studies of the leadership of two Southeast Asian women: Megawati Soekarnoputri in Indonesia and Corazon Aquino in the Philippines. The results show that both Islam and Catholicism have complex histories and interpretations of women's roles in leadership. While conservative and patriarchal readings exist within both traditions, there is also interpretive space that allows women to emerge as leaders. The leadership of Megawati and Aquino demonstrates that women are capable of leading with distinctive styles rooted in values ​​of spirituality, morality, and service. Both demonstrate a non-confrontational yet effective leadership approach, which simultaneously opens up space for reinterpreting women's roles in religion and politics. Thus, women's leadership is not a deviation from religious teachings, but rather part of the socio-religious dynamic that demands inclusivity and equality.